Translation analysis of subtitle from English into Indonesian in The Raid 2 Movie - Rianto Duta Wicaksono; Yuli Kuswardani (English Teaching Journal : A Journal of English Literature, Language and Education, 2019)
Indonesian movies make foreigners interested to watch it. English subtitle is the solution to make Indonesian movies worldwide. Subtitle’s strategies to make good subtitle is very important to make clear subtitle. The objective of the research are to identify subtitling strategies subtitle used in translating The Raid 2 movie and to describe the subtitling clarity of The Raid 2 movie’s English subtitle. The research method used is descriptive approach. The data are required from three source, they are the script of The Raid 2 movie, the reader evaluation and the expert evaluation. This research uses documentation as the technique of collecting data. The researchers use data, investigator, and theory triangulation to make this research can be trusted. The results of this research show that: (1) there are 11 strategies that subtitle used in translating The Raid 2 movie; (2) the clarity of subtitle in The Raid 2 movie is high. The percentage of subtitling clarity from respondents is 91, 02%. The researchers obtain 41 subtitles included into lowest score, 154 subtitles included into medium score, and 681 subtitles included into high score.